Thanatophobia: A Study of Beloved People’s Death in Bradbury’s The Night - Silalahi, Theresia Anggi Angelia; Agustina, Mia Fitria; Trisnawati, Ririn Kurnia (Universitas Dian Nuswantoro, 2024)
The young protagonist Shorts in Ray Bradbury's The Night is the subject of this study, which explores the concept of thanatophobia, or the fear of death. The research analyzes Shorts' experiences with death, including the death of his sister and grandfather, as well as the metaphorical contact with mortality in the ravine, using a qualitative descriptive approach. The data suggest that Shorts interprets death differently at each level, reflecting his developmental understanding and emotional responses. The study emphasizes how environmental triggers, developmental cognitive stages, and familial bonds influence his fear and coping mechanisms. These revelations highlight how crucial open communication and supportive caregiving are in assisting kids in grieving and building resilience. This study provides a greater knowledge of mortality dread in fictional and real-life circumstances by bridging the gap between literary analysis and psychological viewpoints.